The Effects of Holy Name Meditation on Spiritual Well-being, Depression, and Anxiety of Patients with Cancer - Yong, Jinsun; Park, Junyang; Kim, Juhu; Kim, Pyeongman; Seo, Im Sun; Lee, Hun (Journal of Hospice and Palliative Nursing, 2018)
This study was conducted to evaluate the effects of the Holy Name Meditation on cancer patients' spiritual well-being, anxiety, depression, and pain. Twenty-eight patients were enrolled in the control group, and 18 patients were selected for the experimental group. Only the patients in the experimental group completed 5 weeks of the Holy Name Meditation Program. All participants were surveyed to assess spiritual well-being (Spiritual Well-Being Scale), anxiety and depression (Symptom Checklist 90-R), and pain (numeric pain rating scale). There were no significant differences between the two groups' general characteristics, but the baseline survey revealed that anxiety and depression levels were higher in the experimental group. Analyzing the results after controlling the baseline scores of anxiety and depression showed that spiritual well-being was increased (F = 4.80, P =.034), whereas anxiety (F = 4.98, P =.031) and depression (F = 7.28, P =.010) were decreased after the intervention. No difference in pain was found between the two groups. The Holy Name Meditation Program was thus effective in enhancing cancer patients' spiritual well-being and decreasing their anxiety and depression. Therefore, it is recommended that Holy Name Meditation be provided in clinical settings to reduce the psychosocial and spiritual suffering of cancer patients.
Keywords: Adult; Aged; Anxiety; Depression; Female; Humans; Male; Meditation; Middle Aged; Neoplasms; Pain Management; Republic of Korea; Spiritual Therapies; anxiety; cancer; depression; spiritual intervention; spiritual well-being